On the accurate description of uranium metallic phases: A MEAM interatomic potential approach - Fernandez, Julian Roberto (2014)
A new interatomic potential in the framework of the modified embedded atom method (MEAM) to model U metal is presented. The potential acceptably reproduces the lattice parameters and cohesive energy of the orthorhombic αU. The relative stability of the experimentally observed phase at low temperatures with respect to several other structures (bct, bcc, simple cubic, tetragonal β Np, fcc and hcp) is also taken into account. Intrinsic point defect properties compare reasonably well with data from the literature. To determine the quality of the interaction, the potential is used to study a number of properties for the pure metal at finite temperatures and the results are compared with the available data. The obtained allotropic αU↔γU transformation and melting temperatures are in good agreement with experimental values. Based on the simulations, a new αU↔γU transformation mechanism is proposed.